Peran Media Sosial Instagram @KANWILBPNBANTEN Sebagai Pusat Informasi di Bidang Pertanahan : Studi Etnografi Virtual pada Akun Instagram @Kanwilbpnbanten - Mochammad Mirza; Ari Suseno Suseno; Rojviyani Tsaqila (Prisani Cendekia Institute, 2023)
This study aims to analyze and describe the role and use of social media Instagram as an information center in the land sector and the satisfaction obtained after accessing content on the @kanwilbpnbanten account. This study uses the theory of Uses and Gratifications. This study uses a virtual ethnographic research method. Data collection methods in this study are interviews, observation, and documentation. The results of the study show that the role of Instagram social media is as a medium for conveying information about land activities so that it can be widely known by the public. Social media Instagram @kanwilbpnbanten is used as a means of finding information, entertainment, strengthening self-identity and interacting with other users